CORRELATION BETWEEN FEMALE JUNIOR HIGH SCHOOL STUDENTS KNOWLEDGE AND BREAST SELF EXAMINATION BEHAVIOR - Karni, Winda Ayu Juwita; Rostianingsih, Dewi; Sirait, Lenny Irmawaty (Indonesian Midwifery and Health Sciences Journal, 2024)
Background : Breast cancer is a painless lump, can develop and invade surrounding breast tissue then spread to nearby lymph nodes or to other organs in the body. The high mortality rate of breast cancer is due to a lack of knowledge about breast cancer and early detection so that it comes to health services at late stage. As recommended by the government, the most effective screening method is Breast Self Examination which is very easy but many teenagers do not know this method. The aim of this study is to know correlation between students knowledge and Breast Self Examination Behavior. Method : Descriptive quantitative reasearch through a cross sectional approach. Population in this study were 218 female students at Ananda Junior High School Bekasi City West Java in 2022 with 141 students for sample using simple random sampling technique. Research instruments using questionnaires about knowledge of pathophysiology and breast cancer prevention as independent variable and Breast Self Examination behavior as a dependent variable using the chi square statistical test. Results : Majority as many 91.5% of Ananda Junior High School students had never done Breast Self Examination, had poor knowledge about the pathophysiology of breast cancer (93.6%) and breast cancer prevention (83.7%). Then obtained a p value of 0.000 (p < 0.05) which means that there is a significant correlation between knowledge about the pathophysiology and breast cancer prevention with Breast Self Examination  behavior. Conclusion : The proportion of Breast Self Examination behaviour of Ananda Bekasi junior high school students is very low (8.5%). Most respondents had less knowledge about the pathophysiology of breast cancer (93.6%) and breast cancer prevention (83.7%). Suggestions: Conduct ongoing research to see any changes in respondent behavior in the future.